Study on Control of Cumulative Risk for Submarine Tunnel Shield Construction - Kang Meng; Mingda Li; Jing Zhou (Advances in Civil Engineering)
Researching the control of cumulative risk for submarine tunnel shield construction is of great significance for improving risk management capability. Firstly, the concepts of cumulative risk, fragility, and the theory of system dynamics (SD) are introduced. Secondly, the risk conduction network is established, and the risk conduction mechanism based on fragility is analyzed. Then, the cumulative risk control model is established by SD. Finally, Dalian Metro Line 5 Cross-sea Large Diameter Shield Construction Project is used to verify the model. Simulations of cumulative risk with and without control measures are compared, and the result is in line with objective facts. The correctness and effectiveness of the model are verified.